The Physical and Mechanical Properties of Agar and Carrageenan Film Incorporated with Hydrolysate-Konjac Glucomannan - Ploypetchara, Thongkorn; Srimongkoluk, Ubolwanna; Borompichaichartkul, Chaleeda; Lekhavat, Supaporn (Science Essence Journal, 2022)
The effect of combine-polysaccharides ratio on the properties of edible film was studied. The objective of this research is to investigate the physical and mechanical properties of polysaccharide film that incorporated with hydrolysate-konjac glucomannan. Film samples containing agar (0-100%), carrageenan (0-50%), or hydrolysate-konjac glucomannan (HKG) (0-50%) at different calculated ratios of mixing using mixture design and adding glycerol as a plasticizer were prepared. The results showed that viscosity of the film solution was decreased while adding HKG. The addition of HKG could increase thickness and moisture content but could decrease the transparency of the film. The result showed that the highest water vapor permeability (WVP) came from film which contained mixture of HKG and carrageenan (1.22x10-5 g mm m-2 s-1 Pa-1). The lowest WVP came from agar, while the mixture of HKG and carrageenan had the lowest oxygen permeability (OP) (5.84x10-8 mm cm3 m-2 s-1 Pa-1). The mechanical properties in terms of tensile strength and load at the maximum of the film were decreased as addition of HKG but were increased with agar adding. The elongation at break was increased with the mixture of HKG and carrageenan, and the mixture HKG, carrageenan, and agar (32.42%), respectively. In conclusion, the calculated mixture ratio from mixture design contributed to different physical and mechanical properties of the polysaccharide film, depending on their concentrations and type of polysaccharide in the film solution. The mixture of HKG, carrageenan, and agar could be applied for food packaging. However, the barrier behavior of the film need to be improved in future research.